Cor Dera : Guide to Nature. - Kunstverein Ludwigsburg (Amsterdam : Torch Books Amsterdam, 2000)
The artist's book published for the exhibition in Ludwigsburg, Cor Dera's Guide to Nature, is to be seen as a redesignation. A few interventions turn an opulently illustrated volume about nature into an art book (binding, text etc.). And as the title suggests, the artist is taking the reader to nature : he is the nature-guide. The ambiguity inherent in the concept begins to suggest that Cor Dera is both guiding us to nature and guiding nature itself : out of those books.
biog., tent., bibliog. p. 601-603
Duits
Engels
Nederlands
produced on the occasion of the exhibition 'Breaking the ice', from Cor Dera at the Kunstverein Ludwigsburg. 2000-01-23. 2000-03-05
boek
Keywords: Dera, Cor